Stellar and dust emission profiles of IMEGIN galaxies - Nersesian A.; Adam R.; Ade P.; Ajeddig H.; André P.; Artis E.; Aussel H.; Baes M.; Beelen A.; Benoît A.; Berta S.; Bing L.; et al. (EPJ Web of Conferences, 2024)
We present a morphological analysis of a set of spiral galaxies from the NIKA2 Guaranteed Time Large Program, IMEGIN. We have fitted a single Sérsic model on a set of broadband images, from ultra-violet (UV) to millimeter (mm) wavelengths, using the modelling code Statmorph. With the recently acquired NIKA2 1.15- and 2-mm observations, it is possible to extend such a morphological analysis to the mm regime and investigate the two-dimensional (2D) distribution (exponential, Gaussian) of the very cold dust (<15 K). We show preliminary results of the 2D large-scale distribution of stars and dust in spiral galaxies, how they relate to each other, and highlight how they differ from galaxy to galaxy.